2006
DOI: 10.1515/jpm.2006.057
|View full text |Cite
|
Sign up to set email alerts
|

Intrapartum cardiotocography – the dilemma of interpretational variation

Abstract: Inter-observer variation in interpretation of abnormal CTG readings and recommendations for intervention is relatively wide. To improve reliability, uniform classification and standardized training in CTG interpretation are needed, as well as increased use of computerized CTG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 32 publications
3
45
1
1
Order By: Relevance
“…6 Moreover, there is interobserver variation in interpretation of abnormal cardiotocography readings and recommendations for interventions. 7 The study done in 2000 at Lady Dufferin Hospital Karachi, showed that the Apgar score less than 7 at 1 minute in 64.15% cases, and it was more than 7 at 1 minute in 35.84%. It remained less than 7 at 5 minute in 18.86% only, while in 81.13% it improved or stayed constant in pathological CTG group.…”
Section: Introductionmentioning
confidence: 99%
“…6 Moreover, there is interobserver variation in interpretation of abnormal cardiotocography readings and recommendations for interventions. 7 The study done in 2000 at Lady Dufferin Hospital Karachi, showed that the Apgar score less than 7 at 1 minute in 64.15% cases, and it was more than 7 at 1 minute in 35.84%. It remained less than 7 at 5 minute in 18.86% only, while in 81.13% it improved or stayed constant in pathological CTG group.…”
Section: Introductionmentioning
confidence: 99%
“…The original purpose of continuous electronic foetal heart monitoring during labour to monitor the foetus to prevent intrapartum still birth and perinatal morbidity. 4 Intrapartum monitoring tool with high accuracy is required to ensure foetal well-being in labour. Intermittent auscultation of FHR and electronic foetal monitoring such as cardiotocography are most popular methods for intrapartum foetal surveillance, whereas the former focuses only on estimation of basal heart rate, the latter also reflects upon other qualities of foetal heart rate such as variability, accelerations and decelerations.…”
Section: Introductionmentioning
confidence: 99%
“…Computer analysis of CTGs was introduced in the 1980s [9,17,21,24] in an attempt to overcome the subjectivity of visual analysis [3,29] . The fi rst systems were developed for antepartum monitoring, where increased baseline stability, lower signal loss and artefacts and reduced tracing length pose less challenges for signal processing and algorithm development.…”
Section: Discussionmentioning
confidence: 99%
“…Several systems for central monitoring of fetal signals have been developed to provide simultaneous display of multiple tracings on the same computer screen, in one or several locations, thereby allowing easier monitoring of signals. The need to handle digital signals has also allowed the incorporation of computer analysis of the FHR into several of them, with the aim of overcoming the well-known poor reliability of visual analysis [3,29] to prompt healthcare professionals to act on changes that are allegedly associated with fetal hypoxia.…”
Section: Introductionmentioning
confidence: 99%